The Integration of Ontario Birth Centers into Existing Maternal‐Newborn Services: Health Care Provider Experiences. (8th August 2018) - Reszel, Jessica; Sidney, Dana; Peterson, Wendy E.; Darling, Elizabeth K.; Van Wagner, Vicki; Soderstrom, Bobbi; Rogers, Judy; Graves, Erin; Khan, Bushra; Sprague, Ann E.
Abstract : Introduction: In 2014, 2 freestanding, midwifery‐led birth centers opened in Ontario, Canada. The purpose of this study was to qualitatively investigate the integration of the birth centers into the local, preexisting intrapartum systems from the perspective of health care providers and managerial staff. Methods: Focus groups or interviews were conducted with health care providers (paramedics, midwives, nurses, physicians) and managerial staff who had experienced urgent and/or nonurgent maternal or newborn transports from a birth center to one of 4 hospitals in Ottawa or Toronto. A descriptive qualitative approach to data analysis was undertaken. Results: Twenty‐four health care providers and managerial staff participated in a focus group or interview. Participants described positive experiences transporting women and/or newborns from the birth centers to hospitals; these positive experiences were attributed to the collaborative planning, training, and communication that occurred prior to opening the birth centers. The degree of integration was dependent on hospital‐specific characteristics such as history, culture, and the presence or absence of midwifery privileging. Participants described the need for only minor improvements to administrative processes as well as the challenge of keeping large numbers of staff updated with respect to urgent transport policies. Planning and opening of the birth centers was seen as a driving force in further integrating midwifery care and improving interprofessional practice. Discussion: The collaborative approach for the planning and implementation of the birth centers was a key factor in the successful integration into the existing maternal‐newborn system and contributed to improving integrated professional practice among midwives, paramedics, nurses, and physicians. This approach may be used as a template for the integration of other new independent health care facilities and programs into the existing health care system.